From the Blitz to the Boer War, Re-presenting (Inter)National and Colonial Wars and Personal Traumas: Craig Higginson’s The Landscape Painter as a lyrical epic - Mathilde Rogez (Revue LISA)
When he sees the young woman who is going to be the new lodger of the bedsit next to his, Arthur Bailey, an elderly painter who now lives as a recluse in post-World War Two London, is suddenly thrown back into the past. The images of the Boer War which had been haunting him for so long resurface, and become interlaced with those of the Blitz, the ruins of London evoking a Gothic landscape. Written from a country still probing its own wounds almost a century and half later, The Landscape Painter (2011), Craig Higginson’s fourth novel, intertwines representations of conflicts in both the then colony and the metropolis, and combines genres and mediums: in the same way the painter of the title alternates between the sublime and the picturesque, the author mingles the lyrical, the epic and the plaasroman (or farm novel), so as to question traditional national narratives. After a series of wars which have broken the characters’ minds and maimed their bodies, language itself has been affected, disarticulated, so that the novel simultaneously questions how to re-present or commemorate those conflicts, both far and close, (inter)national, colonial and personal, the political and the esthetic being thus intimately entangled.